An experimental study of adolescent sleep restriction during a simulated school week: changes in phase, sleep staging, performance and sleepiness. (21st November 2016) - Agostini, Alex; Carskadon, Mary A.; Dorrian, Jillian; Coussens, Scott; Short, Michelle A.
Summary: This laboratory study investigated the impact of restricted sleep during a simulated school week on circadian phase, sleep stages and daytime functioning. Changes were examined across and within days and during a simulated weekend recovery. Participants were 12 healthy secondary school students (six male) aged 15–17 years [mean = 16.1 years, standard deviation (SD) = 0.9]. After 2 nights with 10 h (21:30–07:30 hours), time in bed was restricted to 5 h for 5 nights (02:30–07:30 hours), then returned to 10 h time in bed for 2 nights (21:30–07:30 hours). Saliva was collected in dim light on the first and last sleep restriction nights to measure melatonin onset phase. Sleep was recorded polysomnographically, and the Psychomotor Vigilance Task (PVT) and Karolinska Sleepiness Scale were undertaken 3‐hourly while awake. Average phase delay measured by melatonin was 3 h (SD = 50 min). Compared to baseline, sleep during the restriction period contained a smaller percentage of Stages 1 and 2 and rapid eye movement (REM) and a greater percentage of Stage 4. PVT lapses increased significantly during sleep restriction and did not return to baseline levels during recovery. Subjective sleepiness showed a similar pattern during restriction, but returned to baseline levels during recovery. Results suggest that sustained attention in adolescents is affected negatively by sleep restriction, particularly in the early morning, and that a weekend of recovery sleep is insufficient to restore performance. The discrepancy between sleepiness ratings and performance may indicate a lack of perception of this residual impairment.